LX‐17 Thermal Decomposition‐Characterization of Solid Residues from Cook‐Off in a Small‐Scale Vessel Under Confinement. Issue 7 (4th May 2021) - Reynolds, John G.; Muetterties, Nicolas K.; Nelson, A. J.; Mason, Harris E.; Moore, Jason S.; Coffee, Keith R.; Kahl, Evan M.
Abstract: Concerns surround whether insensitive (or any) energetic materials are more dangerous to handle when exposed to abnormal thermal environments. This study characterizes the residual material remaining after LX‐17 (92.5 % 1, 3, 5‐triamino 2, 4, 6‐trinitro benzene (TATB) and 7.5 % Kel‐F) is exposed to various thermal environments in a sealed small‐scale vessel cook‐off test reactor (heated at 0.1 to 100 °C/min until the reactor opened at 3000 psi (20.7 MPa)). Previous work has shown no additional sensitivity of these residues as evaluated by small‐scale safety analysis, but characterization on the molecular scale indicates the TATB is transformed to more reactive compounds as well as the residue could be precursors to toxic gases. The solids and chars were characterized by various analytical methods. Heat‐flow measurements indicated exothermic release is due to a mixture of residual TATB and related decomposition products (which may be more energetic). The N/C and O/N ratios indicated a material much more degraded than TATB. Primarily, the solids were a network of amorphous C inter‐dispersed with N and O. Types of bonding include C−C, C−N, N−H, N−C, N=C, N≡C, C−O =, and −OH. Solvent extracts of the solids showed TATB decomposition intermediates benzo‐furazans and benzo‐furoxans, substituted TATB (mono‐nitroso, hydroxyl, and chlorinated) along with several unidentified smaller molecules. These results indicate thermal treatment produces an amorphous carbon residue with heteroatoms incorporated through differing functionality, varying depending upon the thermal severity of exposure. These structures also could further decompose producing toxic light gases (such as cyanide). Abstract :